GROWTH AND YIELD OF EVEN-AGED Cupressus lusitanica PLANTATIONS IN SOUTHERN BRAZIL - Dobner Jr., Mário (Floresta, 2021)
Plantation forestry in southern Brazil demands additional timber species to a higher market differentiation by providing high quality timber and exploitation of market niches. Cupressus lusitanica has long been recognized for this purpose but, until now, it was not properly region-wide quantified in terms of growth and yield. The present study delivers the lacking quantitative approach, which may encourage the commercial use of the species. With this study it was aimed at collecting and processing quantitative data from all known C. lusitanica stands in southern Brazil. Inventories were carried out (60 ha, 6-39 years of age) in order to model the development of dominant height (h100), basal area, volume and dominant diameter (d100). Dominant height was the basis for site quality evaluation, delivering site index curves, which, together with the commercial volume of the stands, allowed yield modelling. A wide amplitude of dominant height growth was detected (10-30 m at 20 years), indicating a great site quality variation. At age of 20 years, commercial volumes of 110 and 620 m³ ha-1 were observed for site indexes of 14 and 26, respectively, equivalent to a maximum of 6-31 m³ ha-1 year-1 at ages between 16-18 years. Results demonstrated in a robust manner that C. lusitanica has a high potential for cultivation in southern Brazil. Thus, offering the opportunity of market differentiation by promoting market niches whose demands timber for special solid end-uses.